One text, various narratives : an investigation into the reception of the Saul narrative of the Hebrew Bible in three reading communities - Mirkin, Nina Yona (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1996.